Analisa Kegagalan Baut Pengikat Pelat Trunnion Linner pada Unit Cement Mill 1 Di PT. X - Hendri, Darwin; Irwansyah, Irwansyah; Susanto, Herdi; Ali, Syurkarni (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
This research aims to identify the causes of the failure of the fastening bolts for the trunnion plate on cement mill unit 1 at PT. X. The research method used is an empirical study consisting of two main phases. The first phase involves identifying the causes of bolt fractures through macroscopic observations to examine the patterns of bolt fractures. The second phase involves analyzing the forces acting on the bolts by calculating the inertial forces generated due to torque tightening, followed by determining the centrifugal forces produced by the ground material and calculating the bending moments affecting the bolts. The results of this research revealed that the main cause of bolt failure is the presence of crack patterns characterized by significant plastic deformation in the bolt body; this type of fracture is categorized as ductile fracture. Analysis of the forces acting on the bolt also revealed that the stress applied to the bolt exceeds its strength capacity. The stress reached 436 MPa, whereas the bolt's strength was only around 330 MPa (yield strength). The findings of this research are expected to serve as initial data for further research that will investigate the metallurgical aspects as a deeper cause of bolt failure.